Skill-based immigration, economic integration, and economic performance - Abdurrahman B. Aydemir (IZA World of Labor, 2020)
There is increasing global competition for high-skilled immigrants, as countries intensify efforts to attract a larger share of the world's talent pool. In this environment, high-skill immigrants are becoming increasingly selective in their choices between alternative destinations. Studies for major immigrant-receiving countries that provide evidence on the comparative economic performance of immigrant classes (skill-, kinship-, and humanitarian-based) show that skill-based immigrants perform better in the labor market. However, there are serious challenges to their economic integration, which highlights a need for complementary immigration and integration policies.
Keywords: J61; J68; 330; immigrant selection; immigration policy; economic outcomes; demand-driven policy; supply-driven policy; point system